KAJIAN SINGKAT MORFOLOGIS ISTILAH-ISTILAH AGAMA HINDU DI BALI - I MADE SUWETA (Purwadita : Jurnal Agama dan Budaya, 2017)
Speaking of Bali as one of the languages of culture, of course, is closely related to religion. People in Bali majority embraced Hinduism. There are many terms or vocabulary in Hinduism. The terms contained in the Hindu religion in society will be a lot of additive or affixation in the pronunciation and also will  have a different meaning. Based on the background that has been described in the datas, the issues raised in this study was formulated in the form of questions as follows: (1) How do the basic words of Balinese language in terms of Hinduism? and (2) How the Bali language morphological system in terms of Hinduism?. The method in this study include methods of data collection by the literature, which is done  by  reading  a  variety  of  resources  related  to  the  terms  of  Hinduism  that  includes  basic words, invented words, repeated words, and compound words. Furthermore, the data that has been analyzed by descriptive synchronic, ie, the analysis done by describing the data found with the words in a narrative. Based  on  this  analysis  obtained  results  of  the  study  as  follows.  There  are  terms  in Hinduism that can be assessed based on the study of morphological, includes basic words (not received  prefixes),  derivatives  (get  the  process  of  affixation,  either  by  adding  a  prefix,  infix, suffix,  and  konfiks),  said  repeated  (repetition),  and compound  word  (a  combination of  two  or more words that generate new meanings).